Transcriptomic analysis in tomato fruit reveals divergences in genes involved in cold stress response and fruit ripening - Mitalo, Oscar W.; Kang, Seung Won; Tran, Long T.; Kubo, Yasutaka; Ariizumi, Tohru; Ezura, Hiroshi (Frontiers in Plant Science, 2023)
Cold storage is widely used to extend the postharvest life of most horticultural crops, including tomatoes, but this practice triggers cold stress and leads to the development of undesirable chilling injury (CI) symptoms. The underlying mechanisms of cold stress response and CI development in fruits remain unclear as they are often intermingled with fruit ripening changes. To gain insight into cold responses in fruits, we examined the effect of the potent ethylene signaling inhibitor 1methylcyclopropene (1-MCP) on fruit ripening, CI occurrence and gene expression in mature green tomatoes during storage at 20ºC and 5ºC. 1-MCP treatments effectively inhibited ethylene production and peel color changes during storage at 20ºC. Storage at 5ºC also inhibited both ethylene production and peel color change; during rewarming at 20ºC, 1-MCP treatments inhibited peel color change but failed to inhibit ethylene production. Furthermore, fruits stored at 5ºC for 14 d developed CI symptoms (surface pitting and decay) during the rewarming period at 20ºC regardless of 1-MCP treatment. Subsequent RNA-Seq analysis revealed that cold stress triggers a large-scale transcriptomic adjustment, as noticeably more genes were differentially expressed at 5ºC (8,406) than at 20ºC (4,814). More importantly, we have found some important divergences among genes involved in fruit ripening (up-or down-regulated at 20ºC; inhibited by 1-MCP treatment) and those involved in cold stress (up-or down-regulated at 5ºC; unaffected by 1-MCP treatment). Transcriptomic adjustments unique to cold stress response were associated with ribosome biogenesis, NcRNA metabolism, DNA methylation, chromatin formation/remodeling, and alternative splicing events. These data should foster further research into cold stress response mechanisms in fruits with the ultimate aim of improving tolerance to low temperature and reduction of CI symptoms during cold storage.